2018
DOI: 10.35139/cantilever.v7i2.67
|View full text |Cite
|
Sign up to set email alerts
|

Simulasi Karakteristik Genangan Banjir Menggunakan Hec-Ras 5 (Studi Kasus Subsistem Sekanak Di Kota Palembang)

Abstract: This paper deals with the modelling and simulation of flood inundation characteristics i.e. boundaries, depths, and velocities within Sekanak Subsystem which is one of flood-prone areas in Palembang City, Indonesia. The area of subsystem being studied was about 11 km 2. The new hydrodynamic model, HEC-RAS 5.0 was used to simulate the flood flow regimes by integrating the one-dimensional and two-dimensional model, known as combined 1D/2D flow model. The geometry of drainage channel was used as 1D domain to simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Therefore, an explanation of the hydrological and hydraulic analysis methods used will not be discussed in more detail here. The detail hydrological modeling and simulation used in this study have been described in the previous study conducted by Al Amin et al (2015), while the hydraulic model and the simulation used in this study in detail can be found in Al Amin et al (2018). The data used in the hydrological analysis include rainfall intensity, river discharge, topography, river network, land use/cover, and soil type, whereas the data used in the hydraulic analysis consists of channel cross-sections, tidal water level, land cover, base map, and digital elevation model (DEM).…”
Section: Flood Hazard Indicatorsmentioning
confidence: 99%
“…Therefore, an explanation of the hydrological and hydraulic analysis methods used will not be discussed in more detail here. The detail hydrological modeling and simulation used in this study have been described in the previous study conducted by Al Amin et al (2015), while the hydraulic model and the simulation used in this study in detail can be found in Al Amin et al (2018). The data used in the hydrological analysis include rainfall intensity, river discharge, topography, river network, land use/cover, and soil type, whereas the data used in the hydraulic analysis consists of channel cross-sections, tidal water level, land cover, base map, and digital elevation model (DEM).…”
Section: Flood Hazard Indicatorsmentioning
confidence: 99%
“…Research on modeling flood-prone areas has been carried out by other researchers with a scoring system on natural factors (parameters) that affect flooding, including meteorological factors (rain intensity, distribution of rainfall, frequency and duration of rain) and characteristics of watersheds (land slope/slope, land height, soil texture and land use) which is then analyzed overlay (map overlay) to see the distribution of flood-prone areas with the help of ArcGIS application [8][9][10][11][12][13][14][15]. In addition, there is also a flood simulation with a certain return period using the HEC-RAS application to see the distribution of floods and flood hazard maps obtained from the results of the analysis using the ArcGIS application [16][17][18][19]. This method is similar to the one used, but in this study combines the data from the river cross-section measurement and DEMNAS then corrects the DEMNAS elevation to match the measurement results, and uses the Diffision Wafe method for 1 second calculation intervals in the 2D HEC-RAS numeric simulation so that the results are more similar to events what happens in the field.…”
Section: Introductionmentioning
confidence: 99%
“…HEC-RAS can simulate the profile of the water surface for varying stable flow and specific levels of flood inundation (Khattak et al, 2015). Many studies have used HEC-RAS software to model floods, such as modeling flood inundation maps based on discharges in the Padang Terap River, Malaysia (Mokhtar et al, 2018), simulating water surface profiles and determining the extent of flood inundation in the Kabul River in Pakistan (Khattak et al, 2015), flood modeling in Godavari River, India (Kute et al, 2014), modeling runoff results from an Artificial Neural Network (ANN) hydrological model downstream of the Baro Akobo River watershed, Ethiopia (Tamiru & Dinka, 2021), and simulating the profile of flood water levels and flood inundation in Sekanak Subsystem, Palembang (Al Amin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%